1991
DOI: 10.1007/bf00218670
|View full text |Cite
|
Sign up to set email alerts
|

History of tonsillectomy and appendectomy in Hodgkin's disease

Abstract: The study comprised all 113 clinically and histologically confirmed cases of Hodgkin's disease aged 15-39 years who were treated at the Department of Hematology of the Faculty of Medicine in Belgrade from January, 1 to June, 30, 1987. For each patient, two individually matched controls were selected. Neighbourhood controls were the first neighbours of the same sex, age, and residence history. Hospital controls consisted of accidentally injured individuals, and they were matched in terms of sex, age, place of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…Contradictory results exist in the literature. Some studies have observed a significant decrease in cellular and humoral immunity, particularly the secretion of immunoglobulin A, and an increase in the incidence of immunomodulatory diseases , but opposing outcomes have also been reported . Bitar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory results exist in the literature. Some studies have observed a significant decrease in cellular and humoral immunity, particularly the secretion of immunoglobulin A, and an increase in the incidence of immunomodulatory diseases , but opposing outcomes have also been reported . Bitar et al .…”
Section: Discussionmentioning
confidence: 99%
“…A prevailing hypothesis for an association between tonsillectomy and Hodgkin's lymphoma (HL) has been that removal of the “lymphoid tissue barrier” would predispose to the development of HL 1. However, so far, epidemiological studies have been conflicting,1, 2 as case–control studies have reported either an increased risk of HL following tonsillectomy1, 3–6 or no association 2, 7–18. One nation‐wide cohort study found a marginally increased risk for all age groups, but a 4‐fold increased HL risk was found for persons tonsillectomized before the age of 12 years 19.…”
mentioning
confidence: 99%
“…Although some studies have linked tonsillectomy with increased risk for Hodgkin's disease (HD) (Vianna et al, 1971;Abramson et al, 1978;Kirchhoff et al, 1980), such findings were not reported in other studies (Johnson and Johnson, 1972;Newell et al, 1973;Gledovic and Radovanovic, 1991). Despite the apparent decline in immunologic function of the tonsils from childhood to adulthood (Brandtzaeg, 1987;Andersson et al, 1994), few studies have investigated the subsequent risk of HD associated with tonsillectomy according to the patient's age at surgery.…”
mentioning
confidence: 99%